Pengaruh e-CRM dan Service Quality terhadap Customer Satisfaction dan Dampaknya terhadap Customer Loyalty pada PT XL - Marshellina, Marshellina; Prabowo, Hartiwi (Binus Business Review, 2013)
This study aims to look at the influence and how much the influence of e-CRM (X1) and Quality of Service (X2) for Customer Satisfaction (Y) that impact on Customer Loyalty (Z) at PT XL. Data collection techniques were with questionnaires, the number of population in this study was approximately three millionrespondents, ie customers who use the product XL in West Jakarta, because the area most widely uses XL provider. Total sample was 100 respondents and the technique used was simple random sampling. The method used in this study was Pearson correlation and path analysis. Based on the results of data analysis, structural equation is Y = 0.310 + 0.330 X1 + X2 0.874 and Z = 0.005 X1 + X2 + 0.449 -0.070 + 0.903 Y, which Electronic Customer Relationship Management and the quality of service have yet to be effective in providing a positive influence for customer loyalty directly, but it must go through prior customer satisfaction as an intervening variable. Therefore, more companies should make improvements to the new way of communicating with customers via electronic media because it gives quite effective results for customer satisfaction in PT XL. Inaddition, PT XL should provide training and better development for the employees working in the company to improve the quality of service that can create customer loyalty.